Transformational leadership practices and excellence in the public family planning sector in Egypt - Hanady Samy Ahmed; Heba Mahmoud Elweshahi; Ayman Ahmed Ragab (Advances in Medical, Pharmaceutical and Dental Research, 2024)
There are current challenges facing Family Planning sector in Egypt. They are significantly associted with population problem in Egypt that might act as a barrier against achieving Egypt Vision 2030. Effective leadership is a window of hope toward resolving such challanges. The study aimed at assessing followers’ perception of transformation leadership at public family planning sector and identify the relation between transformation leadership behavior and achieving excellence.A cross section study included 148 Family planning providers to assess their perception towards commitment of leaders with transformational leadership practices using a structured Transformation leadership questionnaire consist of 20 statments coving the four domains namely idealized influence, inspirational motivation, individual considerations and intellectual stimulation. The mean score for all domains of transformational leadership vary slightly from 2.1 to 2.2 with a minimum of 0 and a maximum of 4. Similarly, the total TSL score ranged from 0.7 to 3 with a mean of 2.2±0.5. The average total score of transformational leadership for providers working at excellence awarded clinics was 2.4 compared to 2.0 for non-excellent clinics and this difference was statistically significant. similar difference was found in all individual domains. The study concluded that a positive but not optimal level of transformational leadership practices in this healthcare setting was perceived by providers. This highlights areas for potential improvement. Developing transformational leadership capabilities could be a key strategy for public family planning settings aiming to improve their operational performance and hence achieving the ultimate goal for such important sector.   Received: 08 August 2024 Accepted: 02 September 2024 Published: 14 October 2024